Analysis of images supplied by Skincam® can record the changes of some scar features that occur over time. Comparisons with the assessments of dermatologist and patients' perception. (6th January 2023) - Maudet, Aurelie; Le Bec, Jessica; Flament, Frederic; Mirassou, Laureen; Caron, Johanna; Negre, Caroline; Delaunay, Caroline; Balooch, Guive; Jang, Eunjoo
Abstract: Objective: The objective of the study was to assess in vivo the validity of a new imaging device in quantifying the scarring process over time and to compare its data with the expertise of dermatologist and patients' self‐appraisals. Materials and Methods: A total of 37 Korean women, aged 20–50 year, with closed scars of different types, were enrolled after a dermatological evaluation. All subjects applied daily a hydrating cream on their scars for 2 months. Images of scars at different times (Day 0, Day 28, and Day 56) were taken and further analyzed, yielding various parameters such as color, luminance, size, volume, and depth of each scar. A dermatologist visually graded, at each time point, the clinical aspect of the scar, and patients were asked to answer to some questions dealing with their self‐examination of their scar. Results: The changes in some scar features that occurred during the application period were quantified and statistically differed from the D0 baseline value. Scars became of reduced size, lighter (Increased luminance), less red, less deep, and less voluminous. Some of these parameters (volume, lightness, smoothness, texture regularity) were statistically different at D28 whereas some others (area, depth, redness) showed significant changes at D56 . Dermatologist expertise and patients' assessments were in high agreement. Conclusion: This methodological approach that uses a dedicated camera associated with image analysis, despite some inherent limits (size of the scar), appears as a valuable aid to surgeons in the management of scars, in the follow‐up of a given procedure or treatment. Beyond scar management, this approach may be extended to other skin disorders such as acne.